Analysis of the Legal Status of Foundations as Legal Entities in Indonesia Based on Law Number 28 of 2004 - Aji, Ahmad Mukri; Yunus, Nur Rohim; Mukri, Syarifah Gustiawati (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2025)
This study examines the legal status of foundations, the legal implications of foundation management exceeding its authority or failing to fulfill its duties, and the obstacles to enforcing the law against foundations that deviate from their obligations. The background of this study is based on the importance of foundations as non-profit legal entities in social, religious, and humanitarian activities. However, there are often deviations in management that are detrimental to the community and undermine the foundation's goals. The study employs a qualitative method, combining a literature-based approach with a normative legal approach. Data were obtained from a comprehensive literature study, encompassing legal literature, scientific journals, laws and regulations, as well as the opinions of legal experts. Law No. 28 of 2004 was analysed in a normative legal manner, focusing on the legal status of foundations and their legal implications. The results of the study indicate that Law No. 28 of 2004 provides legal protection for foundation assets, ensuring that they are used exclusively for social, religious, and humanitarian purposes. However, foundation management can be held personally liable if they abuse their authority or are negligent in their duties. The study also identified obstacles to enforcing the law against foundations that deviate, including weak government supervision, unclear authority between agencies, and a complex bureaucracy. This study emphasises the importance of strengthening effective regulation and oversight so that foundations can carry out their functions by the objectives of their establishment, providing legal certainty and optimal protection for both the community and the foundation itself.Keywords: Foundation; Legal Entity; Legal Status